2011
DOI: 10.1007/s12194-011-0135-0
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the unnecessary dose from the over-range area with a spiral dynamic z-collimator: comparison of beam pitch and detector coverage with 128-detector row CT

Abstract: Our purpose in this study was to assess the radiation dose reduction and the actual exposed scan length of over-range areas using a spiral dynamic z-collimator at different beam pitches and detector coverage. Using glass rod dosimeters, we measured the unilateral over-range scan dose between the beginning of the planned scan range and the beginning of the actual exposed scan range. Scanning was performed at detector coverage of 80.0 and 40.0 mm, with and without the spiral dynamic z-collimator. The dose-saving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In order to reduce the overranging dose, manufacturers introduced dynamic or adaptive collimators to block the dose which is irrelevant for image reconstruction [ 11 13 ]. Dynamic collimators are mechanical blades which move in and out of the radiation area to block the irrelevant radiation.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce the overranging dose, manufacturers introduced dynamic or adaptive collimators to block the dose which is irrelevant for image reconstruction [ 11 13 ]. Dynamic collimators are mechanical blades which move in and out of the radiation area to block the irrelevant radiation.…”
Section: Introductionmentioning
confidence: 99%
“…It is an indispensable mechanism for overranging reduction during volume helical scanning. Shirasaka et al measured overranging in a 128‐detector row CT scanner. Brilliance iCT can also perform helical acquisitions of up to 80 mm coverage.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the increased overranging in MDCT, a dynamic z ‐collimator was installed in advanced CT scanners . Shirasaka et al measured overranging in a 128‐detector row CT scanner (Brilliance iCT; Philips Healthcare, Cleveland, OH, USA) and concluded that the spiral dynamic z ‐collimator is important for unnecessary overrange dose reduction.…”
Section: Introductionmentioning
confidence: 99%